Boosting online purchase intention in high-uncertainty-avoidance societies: A signaling theory approach - Ahmad Samed Al-Adwan; Mohammad Kasem Alrousan; Husam Yaseen; Amer Muflih Alkufahy; Malek Alsoud (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Despite the fact that online purchase intention has been widely investigated, little is known about the e-retailer-based signals used to reduce online customers' uncertainty perception in high-uncertainty-avoidance (UA) societies. Thus, based on signaling and uncertainty literature, this study investigates return policy leniency (RPL), cash on delivery (COD), and social commerce constructs (SCCs) as the costly signals e-retailers use to increase perceived trust and reduce perceived purchase uncertainty among customers in high-UA societies. An analysis of empirical data from 560 e-commerce users from Jordan reveals that RPL, COD, and SCCs are key enablers of customer trust. Furthermore, customer trust is positively associated with customer purchase intention. The implications for both theory and practice are highlighted.
Keywords: 650; signaling theory; cash on delivery; customer trust; online shopping; return policy; uncertainty avoidance